Early-onset metabolic syndrome and cardiovascular risk in polycystic ovary syndrome - Dhyaneshwar M; Priyadarssini M; Latha Chaturvedula; Basu, Sharbari (Asian Journal of Medical Sciences, 2023)
Background: Polycystic ovarian syndrome (PCOS) is a multifactorial endocrine disorder which along with insulin resistance leads to infertility and metabolic syndrome (MetS). This increases the cardiovascular risk in PCOS patients. Aims and Objectives: The study was undertaken with the objective to assess and compare the levels of insulin, HOMA IR, lipoprotein (a), and comprehensive lipid tetrad index (CTLI) in PCOS patients with and without MetS and, thus, to compare the cardiovascular disease risk in the two groups. Materials and Methods: Seventy-one freshly diagnosed cases of women with PCOS were enrolled in the study. The patients were grouped into PCOS with MetS and PCOS without MetS with 32 women in each group, matched by age. Biochemical parameters were analyzed in blood chemistry autoanalysers. Insulin, lipoprotein (a), was estimated using ELISA. HOMA IR and CTLI were calculated using standard formulae. Results: About 48.6% of the patients with PCOS had MetS which developed at a mean age of 25 years. Blood glucose and lipid profile parameters were significantly higher, while high-density lipoprotein levels were lower in the group with MetS. Lipoprotein (a) and CTLI were also significantly higher in PCOS patients with MetS than in those without MetS. Insulin and HOMA IR, though higher in the PCOS with MetS group than in the PCOS without MetS, there was no significant statistical difference. Conclusion: There is a higher risk of developing cardiovascular disease in PCOS women with MetS than in the PCOS women without MetS at a relatively younger age.